Analisis Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Dengan Sosialisasi Pajak Sebagai Variabel Moderasi Dalam Membayar PBB di Desa Sumberpinang Kecamatan Pakusari, Jember - Zhaskia Shavana Justica; Wiwik Fitria Ningsih; Mainatul Ilmi (AKUNTANSI 45, 2026)
This study aims to analyze the influence of tax understanding, tax sanctions, and tax awareness on taxpayer compliance in paying Land and Building Tax (PBB), as well as to examine the role of tax socialization as a moderating variable in the relationship between tax sanctions and taxpayer compliance. The research was conducted in Sumberpinang Village, Pakusari District, Jember Regency, involving 92 respondents selected using purposive sampling. Data were analyzed using multiple linear regression and moderated regression analysis (MRA). The findings reveal that tax understanding, tax sanctions, and tax awareness have a positive and significant effect on taxpayer compliance. Furthermore, tax socialization is proven to significantly strengthen the influence of tax sanctions on taxpayer compliance. These results highlight the importance of strict sanctions and effective socialization in improving taxpayer compliance at the village level.